CRYPTOCURRENCY’S INNOVATIVE AS PAYMENT SOLUTION FOR ZISWAF - Puro, Intan Widia; Sholahuddin, Muhammad; Arfatun (IQTISHADUNA, 2023)
Cryptocurrency has emerged as a disruptive innovation in the realm of payment systems, providing an alternative to traditional fiat currencies. This abstract explores the potential of cryptocurrency as an innovative payment solution specifically tailored for Zakat, Infaq, Sadaqah, and Waqf (ZISWAF) contributions. The objective of this study is to examine the novelty and implications of utilizing cryptocurrency for ZISWAF payments. A mixed-methods approach is employed, combining qualitative interviews with ZISWAF organizations and quantitative data analysis of cryptocurrency transactions. The results reveal several unique aspects of using cryptocurrency for ZISWAF contributions. Firstly, it offers increased transparency and accountability, as blockchain technology ensures a decentralized and immutable ledger. This enhances trust among donors and recipients, leading to greater participation and higher donation rates. Additionally, cryptocurrency enables fast and low-cost cross-border transactions, eliminating the need for intermediaries and reducing transaction fees. The novelty of this research lies in the application of cryptocurrency to ZISWAF payments, which has not been extensively explored in previous studies. By bridging the gap between digital currencies and charitable giving, this research contributes to the existing literature by presenting a new avenue for utilizing cryptocurrency as a means of social impact. The implications of adopting cryptocurrency for ZISWAF payments are significant. Firstly, it facilitates the global reach of ZISWAF organizations, enabling them to attract donors from different parts of the world. Moreover, the integration of cryptocurrency promotes financial inclusion, allowing individuals with limited access to traditional banking systems to participate in charitable giving. Furthermore, the transparency and traceability of cryptocurrency transactions can help combat corruption and ensure that donations are used for their intended purposes. In conclusion, this study highlights the novelty of utilizing cryptocurrency as an innovative payment solution for ZISWAF contributions. The implications of this research extend beyond the ZISWAF sector, demonstrating the potential for cryptocurrency to revolutionize charitable giving and foster social impact.